(untitled) (Antologia di Diritto Pubblico, 2025)
The contribution of Vittorio Emanuele Orlando offers a critical analysis of the theory of the political mandate as the legal foundation of representation. The author rejects the conception of the relationship between voter and elected representative in private law terms, according to the mandate model, asserting that political representation does not stem from a delegation of power from the voters to the elected, but rather from an institutional function governed by the Constitution.